Kemampuan Manajemen Keuangan Pengusaha Kecil Menengah Dan Koperasi Kota Tarakan Terhadap Daya Saing Usaha - Banding, Mappa Panglima (Ekonomika, 2010)
The purpose of this research is to determine the effect of financial management capacity of Small and Medium Enterprise Cooperative In Tarakan City for Business Competitiveness. Research sampling methods using Simple Random Sampling (random) amount to 185 business ownersÂ in the City Of Tarakan with 5% error rate. The data on knowledge of financial management, business scale, business experience, type of business, and the use of financial information collected by disseminating a questionnaire to the leaders or medium business owners in the city of Tarakan. The data analyzed have been tested before the validity and reliability. Test the hypothesis by using: t test thatÂ a test of significance of partial regression coefficients, test F and R Square. The conclusion of this research is the financial management capabilities and Small and Medium Enterprises Cooperative Tarakan City and a significant positive impact on business competitiveness. Â Key Words: Ability of Financial Management, Competitiveness